Pengaruh Dana Desa Melalui Pemberdayaan Masyarakat Untuk Menurunkan Angka Kemiskinan Di Desa Hewokloang Kabupaten Sikka - Margaretha Susanti Bogar; Petrus E. de Rozari; Cicilia Apriliana Tungga (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the effect of village funds through community empowerment in reducing poverty levels in Hewokloang Village, Sikka Regency using a qualitative descriptive approach. This type of research is field research. The informants used in this research consisted of the Acting Village Head, Village Secretary, Village Treasurer, Village Consultative Body and the community receiving aid benefits. Data was collected using observation, interview and documentation techniques. The data sources in this research are primary and secondary data sources. Based on the research results, it shows that the community empowerment program provided by the Hewokloang Village government took the form of assistance for raising pigs, assistance with red ginger plant seeds and the formation of BUMDes. The results of the research show that the community's perspective regarding assistance with pig farming and red ginger plants can reduce poverty rates. But still in the process of development or cultivation, this assistance has the potential to provide additional income because it has a high selling value. Apart from that, based on the results of interviews with BUMDes administrators, the formation of a Village-Owned Enterprise (BUMDes) in Hewokloang Village has the potential to reduce the problem of poverty by managing basic food businesses.